1996
DOI: 10.1258/0956462961917023
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of sexually transmitted diseases as cofactors for HIV-1 transmission

Abstract: The aim of the study was to investigate the association between infection with HIV-1 infection and a history of other sexually transmitted diseases (STD). We were able to match 1295 HIV-1 infected patients who attended St Mary's Hospital between 1985 and 1991 with 1273 seronegative controls on gender, sexual orientation, injecting drug use and age at time of test. The cases were 3 times more likely to have a history of ever having had another STD than the controls: multivariate conditional logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…In fact, a study by Cohan et al (2006) reported that 44% of the 78 study participants had a history of a sexually transmitted infection (STI). STIs increase the risk for HIV infection because they provide a portal of entry for HIV into the body and increase the number of CD41 cells that the HIV virus targets for replication (Beck et al, 1996).…”
Section: High-risk Sexual Behaviorsmentioning
confidence: 99%
“…In fact, a study by Cohan et al (2006) reported that 44% of the 78 study participants had a history of a sexually transmitted infection (STI). STIs increase the risk for HIV infection because they provide a portal of entry for HIV into the body and increase the number of CD41 cells that the HIV virus targets for replication (Beck et al, 1996).…”
Section: High-risk Sexual Behaviorsmentioning
confidence: 99%
“…STDs are a major cause of acute illness, infertility, long-term disability and death, with severe medical and psychological consequences [Beck et al, 1996]. It is estimated that 340 million episodes of curable STDs occur annually worldwide (http:// www.who.ch/whosis/whosis.html).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B (HBV), HIV viruses and Treponema pallidum are among the most important STDs agents. As STDs may increase the risk of HIV infection [Beck et al, 1996], preventing and treating STDs would help reduce the spread of HIV. More than 42 million people worldwide are currently infected with HIV-1 (http://who.int/hiv/pub/epidemiology/ epi2002/en/), 70% of who live in Sub-Saharan Africa [Laurent and Delaporte, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…In some African countries, the prevalence of HSV-2 has been reported to vary between 17 and nearly 70% (13). As HSV-2-induced lesions facilitate the transmission of human immunodeficiency virus (6,32), HSV-2 infection poses an additional threat to these populations.…”
mentioning
confidence: 99%